Characterization of chromatin accessibility with a transposome hypersensitive sites sequencing (THS-seq) assay. Issue 1 (December 2016) - Sos, Brandon; Fung, Ho-Lim; Gao, Derek; Osothprarop, Trina; Kia, Amirali; He, Molly; Zhang, Kun
Abstract Chromatin accessibility capturesin vivo protein-chromosome binding status, and is considered an informative proxy for protein-DNA interactions. DNase I and Tn5 transposase assays require thousands to millions of fresh cells for comprehensive chromatin mapping. Applying Tn5 tagmentation to hundreds of cells results in sparse chromatin maps. We present a transposome hypersensitive sites sequencing assay for highly sensitive characterization of chromatin accessibility. Linear amplification of accessible DNA ends within vitro transcription, coupled with an engineered Tn5 super-mutant, demonstrates improved sensitivity on limited input materials, and accessibility of small regions near distal enhancers, compared with ATAC-seq.